G-fire station : fire simulation from desktop to grid - Pina, António Manuel Silva (2009)
CROSS-Fire is a research project, funded by the Portuguese NGI and led by UMinho, and focused on topics related to decision making to control forest fires and on the porting to the grid of FireStation - a fire growth simulation application. G-FireStation exploits Grid capabilities in order to have a faster execution, to manage large data input/output files, to create a large data base of simulation results and to allow the interactive control of the simulations through a graphical user interface